A Model to Evaluate Content Dimensions in Educational Institutes in order to establish a Knowledge Management System - Dorsa Didehvar (Journal of Global Pharma Technology, 2017)
Organizational knowledge is one of the most important assets of every organization; thus, its optimal management will lead to a comprehensive organizational improvement. Knowledge management is a powerful tool to achieve competitive advantages and it has been experienced that its use in academic environment has many advantages. However, the important issue prior to establishing a knowledge management system is to identify and determine the effective factors on the readiness of organizations to implement this project. Therefore, the main goal of this research is to provide a model to evaluate the readiness level of content dimension of educational centers in order to establish the knowledge management system. This research is a combination of quantitative and qualitative methods; and after exploratory studies, exploratory interviews with experts of knowledge management have been carried out. The data were coded and classified using the methods of grounded theory. As a result, four hundred and ninety two codes were obtained and the main model consisted of 7 main components and 18 sub-components. A questionnaire consisted of 54 questions was used in this research and its validity and reliability was calculated 0.929 through content method and Cronbach’s alpha coefficient respectively. Data were analyzed through confirmatory factor analysis and the final model consisted of six main content dimensions. These dimensions are as follows in terms of importance and priority: Development of educational departments in accordance with environmental knowledge estimated as 1.193, senior management supportive strategies estimated as 0.469, institutionalization of processes and technology knowledge estimated as 0.461, evident and caching technologies estimated as 0.344, knowledge-oriented behaviors estimated as 0.297, participative culture in knowledge creation estimated as 0.237. Furthermore, twenty-eight sub-problems will be extracted in terms of importance and priority.Keywords: Modeling, Content Dimensions, Educational Centers, Knowledge management system’s establishment.